72.5k views
24 votes
-
Factor Completely : 6w2 – 66w – 72

User Rgfvfk Iff
by
4.6k points

2 Answers

8 votes

Answer:

6(w - 12)(w + 1)

Explanation:

6w² - 66w - 72 ← factor out 6 from each term

= 6(w² - 11w - 12) ← factor the quadratic

Consider the factors of the constant term (- 72) which sum to give the coefficient of the w- term (- 11)

The factors are - 12 and + 1 , since

- 12 × 1 = - 12 and - 12 + 1 = - 11 , then

w² - 11w - 12 = (w - 12)(w + 1) , so

6w² - 66w - 72 = 6(w - 12)(w + 1) ← in factored form

User Steve Waters
by
5.0k points
6 votes

Answer:

6w*6w-66*w-72

Hope This Helps!!!

User Reza Akraminejad
by
4.6k points